LANGUAGE AND THEATRICALITY IN UN CAPTIF AMOUREUX BY JEAN GENET - Malak, Ben Hamou (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
This article analyzes two of the numerous sign systems that cross the posthumous text of the writer and playwright Jean Genet, Un captif amoureux, aiming to comprehend how they interlock in a text and what they bring to it. To that end and because of the lack of a unique and precise theory analyzing the sign systems, it was necessary to gather polyvalent theoretical tools addressing the two sign systems in question, namely the language and the theatricality. The tool suggested by Barthes, especially in Mythologies, as the one covering different types of sign systems, enabled a better reading of this work dealing with the Palestinian revolution, and a better comprehension of the primary role that the sign system holds in the reading of a work that deals with a conflict opposing two peoples, two languages, two cultures for the same land.